1996
DOI: 10.1097/00007890-199611270-00011
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Pattern During Rejection and Infection After Liver Transplantation-Improvements in Postoperative Monitoring?

Abstract: Despite improvements in immunosuppression, rejection occurs in 50% of liver transplant patients and may cause significant morbidity. The most frequent cause of death after liver transplantation is severe infection. Determination of the cytokine network may lead to earlier detection of patients at risk for severe rejection and infection. For this purpose, 81 patients with 85 liver transplants were monitored for cytokines and neopterin on a daily basis. During the first postoperative month, 28 patients (34.6%) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Measurement of neopterin levels is a useful early indicator of complications in allograft recipients. In patients who received allografts of tissue such as kidney, liver, pancreas and heart, immunological rejections are indicated by increasing neopterin levels in urine (45) or serum (46)(47)(48), earlier (mean 2 days) than using conventional diagnostic procedures. Similar changes in neopterin levels occur in patients after bone marrow transplantation (49).…”
Section: Diseases Associated With Elevated Neopterin Levelsmentioning
confidence: 99%
“…Measurement of neopterin levels is a useful early indicator of complications in allograft recipients. In patients who received allografts of tissue such as kidney, liver, pancreas and heart, immunological rejections are indicated by increasing neopterin levels in urine (45) or serum (46)(47)(48), earlier (mean 2 days) than using conventional diagnostic procedures. Similar changes in neopterin levels occur in patients after bone marrow transplantation (49).…”
Section: Diseases Associated With Elevated Neopterin Levelsmentioning
confidence: 99%
“…Such T helper subtype 1 (T H 1)-type proinflammatory cytokines as interleukin-2 (IL-2), IL-15, interferon-␥ (IFN-␥), and tumor necrosis factor-␣ (TNF-␣) are associated mainly with graft rejection, whereas such T H 2-type cytokines as IL-4 have been associated with graft acceptance. [5][6][7][8][9][10][11][12] Also, the T H 2-type cytokine IL-10 has been associated with graft tolerance, 13 although some studies have shown an effect in rejection [14][15][16] and others have shown no association. 6,17 Expression of the T H 2-type cytokine IL-6 may be upregulated, 18,19 downregulated, 6 or unchanged 20 with respect to graft rejection.…”
mentioning
confidence: 99%
“…This study investigated whether a genetic predisposition involving polymorphisms of TH1-, TH2-, or regulatory-type cytokine genes was associated with rejection following human liver transplantation. Several polymorphisms in cytokine genes have been investigated for their possible relationship with cytokine production (Platz et al, 1996;Warlé et al, 2002;Shi et al, 2008;Liu et al, 2009;Zhang and Sun, 2010;Rattanasiri et al, 2013) and graft rejection. Polymorphisms of IL10, TNF, and TGFB1 have been reported to be closely linked to AR (Bathgate et al, 2000;Jonsson et al, 2001;Mas et al, 2004;Azarpira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…T helper subtype 1 (TH1)-type proinflammatory cytokines, such as interleukin-2 (IL-2), interferon-g (IFN-g), and tumor necrosis factor-a (TNF-a), are associated with graft rejection, whereas TH2-type cytokines such as IL-10 have been associated with graft tolerance (Platz et al, 1996;Shi et al, 2008;Zhang and Sun, 2010). Although some studies have shown an effect on rejection (Warlé et al, 2002;Rattanasiri et al, 2013), others have shown no association (Conti et al, 1998;Xie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%